2012
DOI: 10.1063/1.3666852
|View full text |Cite
|
Sign up to set email alerts
|

17O excess transfer during the NO2 + O3 → NO3 + O2 reaction

Abstract: The ozone molecule possesses a unique and distinctive (17)O excess (Δ(17)O), which can be transferred to some of the atmospheric molecules via oxidation. This isotopic signal can be used to trace oxidation reactions in the atmosphere. However, such an approach depends on a robust and quantitative understanding of the oxygen transfer mechanism, which is currently lacking for the gas-phase NO(2) + O(3) reaction, an important step in the nocturnal production of atmospheric nitrate. In the present study, the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Studies of isotope transfer during the O 3 + NO 2 ‐ reaction were conducted in the dark and at room temperature in a Pyrex vacuum line (for details, see Savarino et al and Berhanu et al ). Ozone was produced via Tesla discharge in a cylindrical glass trap using pure oxygen (99.9990%) obtained from a commercial tank supplied by Messer (Bad Soden, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of isotope transfer during the O 3 + NO 2 ‐ reaction were conducted in the dark and at room temperature in a Pyrex vacuum line (for details, see Savarino et al and Berhanu et al ). Ozone was produced via Tesla discharge in a cylindrical glass trap using pure oxygen (99.9990%) obtained from a commercial tank supplied by Messer (Bad Soden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To the remaining (major) portion of the ozone, purified helium was added at a pressure of approximately 760 Torr and the combined gas was pumped through a nitrite‐coated filter until the pressure was only 10 Torr. The isotopic equality between the aliquot and the reacting portion of the ozone was verified in a separate experiment . The isotopic composition of both the starting bulk ozone, denoted Δ 17 O(O 3 ) bulk , and the resulting nitrate product were determined separately in order to quantify the transfer of the 17 O‐excess of ozone to the nitrite‐coated filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition that the terrestrial nitrogen footprint needs to be better understood has led to the development of new methodologies to study its behavior, including multi-isotopic measurements. Some of the facets requiring further resolution include (1) depositional rates, (2) chemical tropospheric chemical transformation mechanisms, (3) source variability and quantitative identification, and (4) significance of long-range transport of nitrates (Berhanu et al, 2012;Costa et al, 2011;McCabe et al, 2007;Morin et al, 2007Morin et al, , 2008Morin et al, , 2011. It has been shown that atmospheric aerosol nitrate possesses one of the largest mass-independent oxygen isotopic compositions ( Figure 8) observed in nature (Michalski et al, 2002(Michalski et al, , 2003(Michalski et al, , 2004a(Michalski et al, , 2005a).…”
Section: The Atmospheric Aerosol Nitrate and The Nitrogen Cyclementioning
confidence: 96%
“…It is now known that most oxygen-bearing molecules in the atmosphere (except water) possess mass-independent isotopic compositions (Thiemens, 2006). These molecules include O 2 , O 3 , CO 2 , CO, N 2 O, H 2 O 2 , ClO 4 , as well as aerosol carbonate, nitrate, and sulfate (Berhanu et al, 2012;Costa et al, 2011;Kunasek et al, 2008Kunasek et al, , 2010Shaheen et al, 2010;Thiemens, 2006). Figure 8 displays the mass-independent isotopic composition of most of the molecules that have mass-independent isotopic compositions associated with them.…”
Section: Atmospheric Observations Of Mass-independent Isotopic Composmentioning
confidence: 97%